Effectiveness of foam rolling vs. Manual therapy in postexercise recovery interventions for athletes: a randomized controlled trial - Espí-López, G. V.; Ruescas-Nicolau, M. A.; Castellet-García, M.; Suso-Martí, L.; Cuenca-Martínez, F.; Marques-Sule, E. (The Journal of Strength and Conditioning Research, 2023)
Self-massage using foam rolling (FR) has been posited to have similar benefits as those traditionally associated with manual therapy (MT) but more economical, easy, and efficient. Despite the widespread use of this technique for the recovery of athletes, there is no evidence supporting the effectiveness of FR vs. MT. The purpose of this study was to assess the effects of FR self-massage in athletes after a high-intensity exercise session compared with a MT protocol. A randomized controlled trial was performed. Forty-seven volunteer amateur athletes (22.2 ± 2.5 years, 53.2% men) were divided into 3 groups: a FR group (n = 18, performed FR self-massage), a MT group (n = 15, received a MT protocol), and a control group (n = 14, passive recovery). After an intense exercise session, dynamic balance, lumbar and hip flexibility, and leg dynamic force were assessed before and after the intervention and 1 week later. Results showed that, in the FR group, dynamic balance scores increased for both limbs at postintervention (p = 0.001) and at follow-up (p = 0.001). These scores were higher for the FR group vs. the MT group at postintervention (right limb, p = 0.048) and at follow-up (right limb: p = 0.049; left limb: p = 0.048), although this variable differed at baseline. In all the groups, lumbar flexion increased at postintervention (p < 0.05), although it was only maintained in the FR group at follow-up (p = 0.048). In conclusion, self-massage with FR may be more effective than MT for the recovery of dynamic balance in athletes after intense exercise, although this result should be interpreted with caution. Foam rolling could have a relevant role in postexercise recovery to prevent injuries in athletes.